Strategi Pembelajaran di Pondok Pesantren Ma’hadut Tholabah Babakan Lebaksiu Tegal Pada Era Pandemi Covid-19 - Ikhda Nurnoviyati (Peneliti.net, 2022)
Islamic Boarding School is an educational institution located in the Indonesian community with a coaching model that is full of value education, both religious values ​​and the noble values ​​of the nation. Ma'hadut Tholabah Babakan Islamic Boarding School is a salaf Islamic boarding school (salafiyah) located in Tegal Regency and integrated with formal school education. Ma'hadut Tholabah Babakan Islamic Boarding School is one of the educational institutions that instills religious values, nationalism, religious character, educational context and prevents negative things that occur along with the times. learning methods in the pesantren environment apply the